Kesedaran, penilaian dan penerimaan e-pembelajaran dalam kalangan ahli akademik - Rubiah Omar,; Jamilah Hj. Ahmad, (penerbit ukm, 2009)
This study presents finding from a survey research conducted on the academic staff of Universiti Sains Malaysia (USM) Penang. The main objective of this research is to identify the level of awareness, evaluation and acceptance of e-learning among the university’s academic staff in assisting the teaching and learning process. The quantitative data for this research were collected from 119 respondents. Rogers’ Innovation Diffusion Theory was used as the basis of this study to identify and assess the level of acceptance towards e-learning in education. The study found high level of awareness towards e-learning concepts. It also revealed efforts undertaken by the university’s management to motivate its academic staff to use the e-learning system in their teaching and learning activities. The respondents’ assessment of the relationship between e-learning and the readiness of self-education was satisfactory. Respondents’ acceptance towards the use of e-learning was high because of their understanding of the overall concept and responsibility related to the application of e-learning. Overall, the respondents positively accepted the use of e-learning in assisting their teaching and learning process.